Research progress on mechanisms and applications of Chinese herbal pairs in treating hyperplasia of mammary gland - Liu, Lu; Zhang, Yuxuan; Shen, Wei; Li, Wanyu; Lei, Xudong; Dai, Xiaoyan (Frontiers in Pharmacology, 2026)
Hyperplasia of Mammary gland (HMG), a common gynecological disorder with potential malignant transformation risk, has been effectively treated using Traditional Chinese Medicine (TCM) herbal pairs. This systematic review explores the therapeutic effects and underlying mechanisms of eight classic Traditional Chinese Medicine (TCM) herbal pairs in treating hyperplasia of mammary glands (HMG). A systematic literature search was performed in PubMed (English) and CNKI (Chinese) from January 2010 to August 2025; peer-reviewed studies with clear designs (e.g., animal models, in vitro experiments, clinical case series) focusing on herbal pairs’ pharmacological mechanisms or clinical applications in the treatment of HMG were included. By integrating network pharmacology, molecular biology, preclinical experiments, and clinical evidence, we found that these herbal pairs exert combined regulatory effects through four core pathways: specifically, 1. hormonal regulation by modulating estrogen/progesterone signaling; 2. anti-inflammation by suppressing NF-κB, IL-6, and TNF-α; 3. restoring proliferation-apoptosis balance via PI3K/Akt, MAPK, and Bcl-2/Bax; 4. alleviating oxidative stress by enhancing SOD/GSH-Px activities. Preclinically, they inhibit mammary cell proliferation in a dose-dependent manner; clinically, they alleviate breast pain and reduce breast lumps with an efficacy rate of 70%–85% and fewer side effects than tamoxifen. These findings validate the scientific basis of TCM herbal pair compatibility and support future translational research (e.g., multi-center randomized controlled trials).